FRI0300 Baseline Characteristics and Pattern of TOCILIZUMAB Use in Patients with Rheumatoid Arthritis: Interim Results from the Multinational, Observational ACT-UP Study. (10th June 2014) - Haraoui, B.; Casado, G.; Theander, E.; Czirják, L.; Taylor, A.; Button, P.; Hinsch Gylvin, L.; Caporali, R.
Abstract : Background: Tocilizumab (TCZ), an IL-6 receptor inhibitor, has been approved in combination with disease-modifying antirheumatic drugs (DMARDs) or as monotherapy for the treatment of adults with rheumatoid arthritis (RA). 1 ACT-UP is an ongoing observational study in 20 countries investigating TCZ use in patients (pts) with RA treated in routine care setups. Objectives: To present interim data on baseline characteristics and pattern of IV TCZ use after 6 months of treatment in the ACT-UP global population. Methods: Adult pts with moderate to severe RA starting TCZ treatment within ≤8 weeks of study enrollment were observed in clinical practice for 6 months. No specific dosing regimen was stipulated; concomitant treatments for RA were allowed. No interventional procedures, clinic visits, or laboratory analyses other than those used in routine practice were performed. The primary objective was to observe patterns of IV TCZ use in RA pts and adherence to licensed label recommendations. Results: Data are presented for 552 pts enrolled in 14 countries as of January 31, 2013; 216 pts (39.1%) started TCZ as monotherapy, and 336 pts (60.9%) started TCZ in combination with a DMARD. Most (93.1%) received an initial TCZ dose of 8 mg/kg. At baseline, more combination therapy than monotherapy pts were taking corticosteroids (55.1% vs 35.2%) and had been previously exposed to a biologic (64.9% vs 51.9%). Lack of efficacy (74.4%) and adverse events (AEs) (12.7%) were the most common reasons for stopping a previous biologic. At baseline, more monotherapy than combination therapy pts had received and stopped previous DMARD treatment (72.2% vs 64.9%). Lack of efficacy and intolerance were the most common reasons for stopping previous DMARDS (41.6% and 31.8% of DMARDS, respectively). Baseline disease activity parameters were similar between treatment groups (Table). Six months after TCZ initiation, 71.8% of monotherapy and 84.2% of combination therapy pts remained on TCZ, with most (92.5%) still receiving 8 mg/kg. During the study, 21 (9.7%) monotherapy and 31 (9.2%) combination therapy pts increased the TCZ dose; 19 (8.8%) monotherapy and 40 (11.9%) combination therapy pts decreased the TCZ dose. Lack of efficacy and AEs, respectively, were cited by 18.5% (5 pts) and 29.6% (8 pts) of monotherapy pts and 6.5% (3 pts) and 43.5% (20 pts) of combination therapy pts as the reason for dose modification. If an AE required dose modification or a laboratory value required follow-up, label recommendations were followed 96.2% of the time. Conclusions: In this multinational, real-life, observational study, 39% of pts were prescribed TCZ monotherapy. In almost 50% of the monotherapy pts and more than 33% of the combination group, TCZ was the first prescribed biologic agent. TCZ monotherapy and combination therapy were well tolerated. References: RoActemra 20 mg/ml concentrate for solution for infusion SPC. Basel, Switzerland: Roche Registration Limited; 2011. Disclosure of Interest: B. Haraoui Grant/research support: AbbVie, Amgen, BMS, Janssen, Roche, UCB, Consultant for: AbbVie, Amgen, BMS, Janssen, Pfizer, Roche, UCB, G. Casado Consultant for: Abbott, Pfizer, Janssen, Roche, GSK, E. Theander Consultant for: Roche, L. Czirják Consultant for: AbbVie, Pfizer, Roche, UCB, MSD, A. Taylor Consultant for: AbbVie, Roche, Celgene, Janssen, BMS, UCB, Speakers bureau: AbbVie, Roche, Janssen, BMS, UCB, P. Button Employee of: Roche, L. Hinsch Gylvin Employee of: Roche, R. Caporali Consultant for: Abbvie, BMS, Roche, UCB, MSD DOI: 10.1136/annrheumdis-2014-eular.2998